Transient reducing greenhouse warming on early Mars. Issue 2 (21st January 2017) - Wordsworth, R.; Kalugina, Y.; Lokshtanov, S.; Vigasin, A.; Ehlmann, B.; Head, J.; Sanders, C.; Wang, H.
Abstract: The evidence for abundant liquid water on early Mars despite the faint young Sun is a long‐standing problem in planetary research. Here we present new ab initio spectroscopic and line‐by‐line climate calculations of the warming potential of reduced atmospheres on early Mars. We show that the strength of both CO2 –H2 and CO2 –CH4 collision‐induced absorption (CIA) has previously been significantly underestimated. Contrary to previous expectations, methane could have acted as a powerful greenhouse gas on early Mars due to CO2 –CH4 CIA in the critical 250–500 cm −1 spectral window region. In atmospheres of 0.5 bar CO2 or more, percent levels of H2 or CH4 raise annual mean surface temperatures by tens of degrees, with temperatures reaching 273 K for pressures of 1.25–2 bars and 2–10% of H2 and CH4 . Methane and hydrogen produced following aqueous alteration of Mars' crust could have combined with volcanically outgassed CO2 to form transient atmospheres of this composition 4.5–3.5 Ga. Our results also suggest that inhabited exoplanets could retain surface liquid water at significant distances from their host stars. Key Points: New ab initio and line‐by‐line calculations show that warming by H2 in CO2 atmospheres is far stronger than previously believed Contrary to previous research, we show that methane could also have been an effective greenhouse gas on early Mars Reducing atmospheres could have been produced transiently by a combination of aqueous alteration of Mars' crust and volcanic CO2 outgassing